Empowering Seventh-Grade Students with Crossword Puzzle for Vocabulary Mastery - Ilma, Wafida Nur; Hastini, Hastini (MASI Mandiri Edukasi, 2024)
Students often struggle with mastering vocabulary in their English learning journey, necessitating English teachers to seek solutions. One viable strategy teachers can adopt is the integration of crossword puzzles to enhance students’ vocabulary mastery. Specifically, the study sought to determine if providing crossword puzzles to the SMP Negeri 3 Banawa seventh-grade students could enhance their vocabulary proficiency. To measure the impact of this approach, the researcher employed pre-test and post-test assessments as evaluation tools in a quasi-experimental study. Through purposive sampling, the researcher selected two classes, VII B and VII D, each with 29 students, as the study’s sample groups. Subsequently, data analysis revealed a significant disparity between the pre-test and post-test scores in the experimental class. Notably, the computed p-valued (two-tailed) was 0.000, falling below the predetermined significance level of 0.05, signifying the acceptance of the hypothesis. In conclusion, implementing the crossword puzzle in this study led to a noticeable improvement in the vocabulary mastery of seventh-grade students at SMP Negeri 3 Banawa.